TEACHING ADVERBS IN ENGLISH LANGUAGE EDUCATION: A PRACTICAL APPROACH - Asatullayeva Mohinur (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the multifaceted role of adverbs in English, emphasizing their importance for adding nuance and precision to language. It delves into various types of adverbs, including adverbs of manner, time, place, frequency, and degree, and how they modify verbs, adjectives, and other adverbs. The paper presents practical teaching methodologies, focusing on interactive activities, contextualized examples, and technological tools to overcome the challenges learners often face. By promoting a systematic and engaging approach to adverb instruction, this article aims to improve learners’ understanding and effective use of adverbs, enhancing their overall English language proficiency.